Fluorinated cyclometalated iridium(iii) complexes as mitochondria-targeted theranostic anticancer agents. Issue 20 (10th May 2017) - Ouyang, Miao; Zeng, Leli; Huang, Huaiyi; Jin, Chengzhi; Liu, Jiangping; Chen, Yu; Ji, Liangnian; Chao, Hui
Abstract : Cyclometalated iridium(iii ) complexes bearing different numbers of fluorine atoms were developed to induce apoptosis via mitochondrial pathways and demonstrated much better anticancer activities than the widely used clinical chemotherapeutic agent cisplatin. Abstract : Six cyclometalated iridium(iii ) complexes bearing different numbers of fluorine atoms were synthesized. These complexes demonstrated much better anti-proliferation activities towards five tumour cell lines than the widely used clinical chemotherapeutic agent cisplatin. Moreover, the anti-proliferation activities were correlated to the number of substituted fluorine atoms. Colocalization and inductively coupled plasma-mass spectrometry (ICP-MS) indicated that this series of complexes could penetrate cell membranes rapidly and preferentially target mitochondria. Manifesting high selectivity between tumour cells and normal cells and remarkable sensitivity to a cisplatin-resistant cell line (A549R), complexIr6 was successfully developed as a novel anticancer agent (with IC50 values of 0.5 ± 0.1 μM for HeLa, 1.1 ± 0.2 μM for HepG2, 1.5 ± 0.3 μM for BEL-7402, 0.8 ± 0.1 μM for A549, and 0.7 ± 0.2 μM for A549R cell lines). Further mechanism studies including mitochondrial membrane potential depolarization and caspase 3/7 activation revealed thatIr6 induced apoptosis via mitochondrial pathways. These results demonstrated that complexIr6 might be a promising candidate as a mitochondria-targeted theranostic anticancer agent.